Application of volumetric method to the assessment of damage induced by action of foreign object on gas pipes - Adib, R.; Schmitt, C.; Pluvinage, G. (Проблемы прочности, 2006)
Gas pipes are submitted to three major types of damage: damages induced by impact of foreign objects, pits and craters produced by corrosion, weld defects produced during manufacturing. Damages induced by impact of foreign objects are considered as the most important problem for the gas pipes reliability and lead to dents, gouges or notches at the pipe failure. Geometrical effect of gauges or notches on brittle or elastoplastic failure of pipes submitted to internal pressure can be treated by the volumetric method. The volumetric method has been applied to a gas pipe submitted to internal pressure and exhibiting a longitudinal external and surface notch. We introduced a special procedure (SINTAP), which allows one to compute the safety factor value. Відомо три основні типи пошкодження труб газопроводів. Найбільш небезпечними з точки зору надійності газових трубопроводів є пошкодження внаслідок дії сторонніх предметів. Запропоновано об’ємний метод, який дозволяє враховувати вплив геометричного ефекту появи вибоїн та концентраторів напружень у трубах на характеристики крихкого або пружно-пластичного руйнування труб, що зазнають дії внутрішнього тиску. Розглянуто використання об’ємного методу за наявності зовнішнього поздовжнього поверхневого концентратора напружень у газовій трубі. Описано спеціальну методику SINTAP, за допомогою якої можна знайти коефіцієнт запасу міцності. Известны три основных типа повреждения труб газопроводов. Наибольшую опасность с точки зрения надежности газовых трубопроводов представляют повреждения, вызванные воздействием инородных предметов. Предложен объемный метод, который позволяет учитывать влияние геометрического эффекта появления выбоин и концентраторов напряжений в трубах на характеристики хрупкого или упругопластического разрушения труб, подвергнутых внутреннему давлению. Рассмотрено применение объемного метода при наличии внешнего продольного поверхностного концентратора напряжения в газовой трубе. Описана специальная методика SINTAP, с помощью которой можно вычислить значение коэффициента запаса прочности.